A comparison study between combination of 50% trichloroacetic acid (TCA) and intralesional meglumine antimoniate (MA) versus intralesional meglumine antimoniate (MA) alone in the treated of cutaneous leishmaniasis - خدام جمال (Latakia University Journal -Medical Sciences Series, 2022)
Background: Cutaneous leishmaniasis is a parasitic disease. It is considered an endemic disease in Syria and causes an important health problem due to the defective scars, which leave in the absence of treatment. Objective: This study was conducted to compare the efficacy of 50% trichloroacetic acid (TCA) and intralesional meglumine antimoniate (MA) versus intralesional meglumine antimoniate (MA) in patients of cutaneous leishmaniasis (CL). Methods: It was an analytical study, conducted in department of Dermatology and Venerology, Tishreen University Hospital, Lattakia, between September 2020 to December 2021. A total of 50 patients were taken in this study. Group I (25 patients) received 50% TCA locally once a week for 6 weeks with intralesional injection meglumine antimoniate till blanching once a week for 6 weeks, and group II (25 patients) was treated with intralesional injection meglumine antimoniate alone. Results: Efficacy was observed in patients 23 (92%) of group I and in 19 patients (76%) of group II (P-value =0.028). Conclusion: The study showed that combination therapy with TCA 50% locally and intralesional MA gave better results in comparison to the patients treated with intralesional MA alone.